Synthesis and characterization of poly(3-hexylthiophene): improvement of regioregularity and energy band gap - Ansari, Muhammad Azhar; Mohiuddin, Shaikh; Kandemirli, Fatma; Malik, Muhammad Imran (Royal Society of Chemistry (RSC), 2018)
The regioregularity and band gap of P3HT, an organic solar cell donor polymer, were improved. Oxidative coupling enhanced regioregularity, voltammetric p-doping broadened the optical absorption band and a molar mass increase reduced the band gap.
Keywords: Chemistry; 7. Clean energy